Il comprendere in educazione - Roberto Travaglini (Studi sulla Formazione, 2025)
The article examines the cognitive process underlying understanding in the educational environment, starting from a neo-cognitivist assumption of Gardnerian inspiration, according to which such a process, in disagreement with a now anachronistic passive vision of the mind (all behaviourist), produces an important inner transformation: understanding (both of the teacher and the student) involves specific, as well as complex theoretical-operational and strategic-methodological dynamisms adopted during didactic communication, such that a cognitive leap of knowledge can be made in view of the realization of a metacognitive process.